2019
DOI: 10.1038/s41598-018-37550-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Response of Acellular Porcine Pericardial for Tissue Engineered Transcatheter Aortic Valves

Abstract: Current heart valve prostheses have limitations that include durability, inability to grow in pediatric patients, and lifelong anticoagulation. Transcatheter aortic valve replacements are minimally invasive procedures, and therefore have emerged as an alternative to traditional valve prostheses. In this experiment, the regenerative capacity of potential tissue engineered transcatheter valve scaffolds (1) acellular porcine pericardium and (2) mesenchymal stem cell-seeded acellular porcine pericardium were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The presence of macrophages and multinuclear giant cells contribute to the biodegradation of biomaterials and to tissue regeneration. Reza et al implanted APP subcutaneously in a mouse dorsum model and found angiogenesis and M2 macrophages recruitment that were closely related to tissue regeneration (Reza Khorramirouz, Noble, Morse, Lerman, & Young, 2019). Rothemal et al applied APP as the barrier membrane in canine ridge preservation, and found that APP facilitated early vascularization and integration with the surrounding tissues (Daniel Rothamel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of macrophages and multinuclear giant cells contribute to the biodegradation of biomaterials and to tissue regeneration. Reza et al implanted APP subcutaneously in a mouse dorsum model and found angiogenesis and M2 macrophages recruitment that were closely related to tissue regeneration (Reza Khorramirouz, Noble, Morse, Lerman, & Young, 2019). Rothemal et al applied APP as the barrier membrane in canine ridge preservation, and found that APP facilitated early vascularization and integration with the surrounding tissues (Daniel Rothamel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, transcatheter TEHVs, derived from porcine pericardium, were implanted in the subcutaneous tissue of rats and demonstrated limited inflammation and a loss of mechanical properties over the first few weeks post-implantation. These valves, however, were not tested in a functional biological position ( 42 ). Development of the large animal model presented in this work will allow for a deeper understanding of these biological mechanisms, as well as the critical design parameters needed to design an ideal TEHV, such as degradation profile and inflammatory status ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, a little is known about the multipotent properties of pericardial MSCs. Most of the reported studies are focused on the hydrogel embedded implantation of a new form of adult cardiac stem cells, as called cardiospheres (CSPs), into the pericardial cavity (16,34) or using the de-cellularized pericardium membrane as a scaffold for MSCs culturing (10,14). The CSPs is a new approach of stem cell therapy for myocardial infarction treatment, using the ability of those cells to differentiate into cardiomyocytes in vivo (34).…”
Section: Discussionmentioning
confidence: 99%